Quality assessment of clinical practice guidelines on psychological distress of cancer patients using the AGREE II instrument - Hao, Ran; Jin, Haoyu; Zuo, Jinfan; Zhao, Rumeng; Hu, Jie; Qi, Yixin (Frontiers in Oncology, 2022)
Objective: This study aimed to assess the quality of the clinical practice guidelines on psychological distress among cancer patients and provide users with recommendations for coping with psychological distress. Methods: A systematic search of relevant clinical practice guidelines was undertaken to identify and select the clinical practice guidelines related to psychological distress among cancer patients. Literature databases were searched in PubMed, Web of Science, Excerpta Medica Database, the Cumulative Index to Nursing & Allied Health Literature, China Biology Medicine, China National Knowledge Infrastructure, WanFang and Weipu Journal Database. The guideline databases include Yimaitong Guidelines Network, National Guideline Clearinghouse, National Institute for Health and Clinical Excellence, American Society of Clinical Oncology (ASCO), New Zealand Guidelines Group, Scottish Intercollegiate GuidelinesNetwork, American Psychological Association, Registered Nurses' Association of Ontario and Cancer Care Ontario (CCO). Four independent reviewers assessed the eligible guidelines using the Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument. Results: Six clinical practice guidelines were included and assessed for critical evaluation. The median score for the scope and purpose domain was 71.5% (IQR 64%-77.25%), the stakeholder involvement domain was 65% (IQR 47.5%-74.5%), the rigour of the development domain was 61.5% (IQR 45.5%-85.25%), the clarity of the presentation domain was 91% (IQR 72.25%-94.5%), the applicability domain was 70% (IQR 33%-78.75%), and the editorial independence domain was 48.84% (IQR 61.75%-95%). Four guidelines (ASCO, 2014; Canadian Association of Psychosocial Oncology, 2015; NCCN, 2020, and CCO, 2016) were classified as “recommended,” and the remaining (European Palliative Care Research Collaborative and Chinese Psychosocial Oncology Society) were “recommended with modifications,” especially in the domains of Stakeholder involvement, rigour of development, and applicability. The inter-rater consistency of each domain showed moderate level (0.52–0.90) analyzing by intraclass correlation analysis. Conclusions: The clinical practice guidelines on psychological distress among cancer patients varied in quality, and there were discrepancies in terms of the recommendations and recommendation grades. These findings could contribute to improving the quality of clinical practice guidelines on psychological distress, and enable the development and implementation of evidence-based guidelines for cancer patients.